2023
DOI: 10.1097/yco.0000000000000846
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammatory syndromes in children

Abstract: Purpose of reviewNeuropsychiatric symptoms due to paediatric neuroinflammatory diseases are increasingly recognized and reported. Psychiatrists are crucial in front-lines identification, diagnosis and care of individuals with disorders such as autoimmune encephalitis and management of long-term neurobehavioral sequelae. This review summarizes recent literature on autoimmune and post-infectious encephalitis, discusses special considerations in children with neurodevelopmental conditions and presents a paradigm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…[21][22][23][24] Cognitive decline, confusion, impaired motor abilities, tremors, sensory changes, ataxia, and seizures are symptoms of neuroinflammatory and neurovegetative diseases such as stroke, Parkinson's disease, Alzheimer's disease, multiple sclerosis, and epilepsy. [25][26][27] The adverse responses to cyclizine are similar to such symptoms, which are induced by macrophage activation. In this study, we found that cyclizine induced the generation of proinflammatory cytokines (i.e., TNF-α, IL-1β, and IL-6) in RAW264.7 macrophage cells.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…[21][22][23][24] Cognitive decline, confusion, impaired motor abilities, tremors, sensory changes, ataxia, and seizures are symptoms of neuroinflammatory and neurovegetative diseases such as stroke, Parkinson's disease, Alzheimer's disease, multiple sclerosis, and epilepsy. [25][26][27] The adverse responses to cyclizine are similar to such symptoms, which are induced by macrophage activation. In this study, we found that cyclizine induced the generation of proinflammatory cytokines (i.e., TNF-α, IL-1β, and IL-6) in RAW264.7 macrophage cells.…”
Section: Discussionmentioning
confidence: 94%
“…However, macrophage overactivation can also lead to acute and chronic inflammatory diseases, such as neuroinflammation, neurodegenerative disease, inflammatory bowel disease, pneumonia, and pulmonary fibrosis 21–24 . Cognitive decline, confusion, impaired motor abilities, tremors, sensory changes, ataxia, and seizures are symptoms of neuroinflammatory and neurovegetative diseases such as stroke, Parkinson's disease, Alzheimer's disease, multiple sclerosis, and epilepsy 25–27 . The adverse responses to cyclizine are similar to such symptoms, which are induced by macrophage activation.…”
Section: Discussionmentioning
confidence: 99%